Hydrogen evolution electrode for AEM electrolytic cell cathode and preparation method of hydrogen evolution electrode

By using multi -layer structured hydrogen analysis electrodes in the AEM electrolytic grooves, using physical gas deposition and doping elements to form a porous network structure, solving the problem of relief and corrosion of the hydrogen ions surface of the AEM electrolytic groove in a strong alkali environment, and realized the electrode. Efficiency and catalytic performance.

CN119372708AActive Publication Date: 2025-01-28SHANGHAI ZHIZHEN NEW ENERGY EQUIP CO LTD

Patent Information

Application Number
CN202411975560.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The AEM electrolytic cell has problems of hydrogen ions surface dissociation and corrosion under a strong alkali environment, and the prior art has not effectively solved these problems.

Method used

The multi -layer structure analysis of the hydrogen analysis of the multi -layer structure of the base network, the bottom layer of the metal, and the catalytic layer is used to form a metal underlying layer and a catalytic layer through physical gas deposition. The doped element is used to form a porous network structure to improve the corrosion resistance and catalytic performance of the electrode.

Benefits of technology

It significantly improves the corrosion resistance and catalytic effect of the electrode in alkaline environments, reduces the reaction of the potential, and improves the stability and life of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372708A_ABST
    Figure CN119372708A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogen evolution electrode for an AEM electrolytic cell cathode and a preparation method thereof, the electrode sequentially comprises a substrate net, a metal bottom layer and a catalyst layer, the substrate net is selected from a stainless steel net or a nickel net, the metal bottom layer is formed on the substrate net through physical vapor deposition, and the material is selected from Ni, Ti, alloys thereof or oxides thereof; the catalytic layer is deposited on the metal bottom layer through physical vapor deposition and sequentially comprises a catalytic bottom layer, a catalytic middle layer and a catalytic outer layer, and the porosity is gradually increased. The preparation method comprises the following steps: roughening the acid etching surface of a substrate net, forming a metal bottom layer on the substrate net through physical vapor deposition, sequentially forming a catalytic bottom layer, a catalytic middle layer and a catalytic outer layer on the surface of the metal bottom layer through physical vapor deposition to obtain a catalytic layer, and performing post-treatment on the catalytic layer through plasmas doped with elements to form a porous network structure. And the corrosion resistance and the catalytic effect of the AEM electrolytic cell cathode in an alkaline environment are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a hydrogen evolution electrode for an AEM electrolytic cell cathode and a preparation method thereof. Background Art

[0002] At present, the mainstream water electrolysis hydrogen production technologies mainly include alkaline water electrolysis (AWE), solid oxide electrolysis cell (SOEC) technology, proton exchange membrane water electrolysis (PEMWE) and anion exchange membrane water electrolysis (AEMWE). Among them, AWE technology has the highest commercial maturity, and the anode and cathode electrode plates do not contain precious metals, and the cost of the electrolyzer is relatively low. However, due to the low catalytic activity of the electrodes, the diaphragm is affected by high ohmic losses, resulting in a low maximum operating current density. In addition, the AWE electrolyzer starts slowly and has poor operating safety under fluctuating conditions. It can usually only be used under stable power input and is not suitable for intermittent electricity such as wind and solar. SOEC technology has attracted much attention due to its high efficiency and environmental friendliness, but due to the high operating temperature (500~1000℃), the durability of ceramic materials is insufficient and the system design is complex. It is still in the laboratory research stage. PEMWE technology has developed rapidly in recent years and has been initially commercialized. It uses proton exchange membrane (PEM) as a solid electrolyte. Since the polymer electrolyte membrane has low gas permeability and rapid response of protons across the membrane to power input, the PEM electrolyzer has the advantages of fast dynamic response, wide load range, large operating current density, high output hydrogen pressure, and compact system structure. It is particularly suitable for hydrogen production coupled with renewable energy power generation systems. However, since the PEM electrolyzer operates in a highly acidic and highly oxidizing environment, the equipment relies on expensive metal materials such as iridium, platinum, and titanium. The high cost is the key to restricting its large-scale development. The AEMWE technology has both the two advantages of AWE low cost and PEMWE high dynamic response. It has received widespread attention in the industry in recent years. Although it is still in the early stages of industrialization, it is expected to become the most promising large-scale renewable energy water electrolysis hydrogen production technology.

[0003] Anion exchange membrane (AEM) electrolyzer is mainly composed of an AEM catalyst layer and a sealed combination of bipolar plates (BP). In AEM electrolyzers, gas diffusion electrode (GDE) and catalyst coated membrane (CCM) are two different membrane electrode (MEA) preparation technologies. CCM technology is to deposit the catalyst directly on the ion membrane to form a catalyst coating membrane, that is, to mix the catalyst powder and ionomer with a suitable solvent and directly coat it on the membrane. The preparation process is relatively complicated and requires precise control of the coating amount and uniformity of the catalyst. The stability of the membrane may be affected by the catalyst deposition process. GDE technology usually deposits the catalyst on a gas diffusion layer (GDL) or a porous transport layer (PTL). The preparation process is relatively simple and easy to achieve large-scale production. In addition, GDE technology improves the rate and efficiency of water electrolysis and the effective utilization of catalysts by optimizing the electrode structure for uniform distribution and transmission of the reaction gas.

[0004] The working principle of AEM electrolyzer is similar to other principles of hydrogen production by electrolysis of water, such as Figure 5 As shown, there are two half reactions involved: oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). The alkaline water splitting reaction and its thermodynamic potential are shown below: Cathode: 2H2O+4e - →2H2+4OH - , E0=-0.828V; Anode: 4OH - →O2+ 2H2O +4e - , E0=0.401V; Overall reaction: 2H2O→2H2+O2, E0=1.23V; Using a high concentration alkaline solution as the electrolyte, the electrolysis device electrochemically decomposes water and produces oxygen and hydrogen, generally driven by a voltage of 1.8 to 2.5 V. In the AEM electrolyzer, the cathode reaction is the key limitation, mainly because the reaction medium in the AEM electrolyzer is water or an acidic environment. The hydrogen evolution reaction is a two-electron catalytic process of hydrogen ions with relatively fast kinetics. However, in an alkaline environment, since water dissociation occurs at the cathode and most of the environment is alkaline, the HER reaction in the AEM electrolyzer is relatively slow.

[0005] In the prior art, the electrode materials of the porous diffusion layer of the hydrogen evolution cathode are mostly selected from materials with high catalytic activity and porosity, such as nickel and its alloys. These materials are not only catalytically active, but also widely available and low in cost. In order to improve the conductivity and mechanical strength of the electrode, some conductive and reinforcing materials are sometimes added to the material, but the degree of commercial application is low, mainly because the material stability is poor in an alkaline environment, and the long-life durable process is very easy to increase the potential. For example, patent document CN117026272A discloses a PEM electrolysis hydrogen cathode diffusion layer and a preparation method thereof, in situ preparing a graphene film as a buffer layer on a titanium felt, and forming a gradient pore structure in the diffusion layer by changing the graphene fiber diameter of the graphene film, accelerating the gas-liquid transmission speed, but not taking into account the corrosion effect of the alkaline environment. Patent document CN118704037A discloses a cathode electrode for alkaline water electrolysis hydrogen production containing a transition layer, which is composed of a porous carbon / carbon composite material matrix, a transition layer and a water electrolysis catalyst layer. The transition layer is located between the porous carbon / carbon composite material matrix and the water electrolysis catalyst layer. The presence of the transition layer not only improves the conductivity of the porous carbon / carbon composite material matrix, but also synergizes with the water electrolysis catalyst to improve the hydrogen evolution catalytic performance. However, the above-mentioned prior art still has the following defects: 1) The problem of hydrogen ion deficiency in an alkaline environment is not considered, and the di-electron reaction essentially requires hydrogen ion reaction; 2) The electrode material does not consider the corrosion problem in an alkaline environment; 3) The electrode structure does not consider the difference between the contact surface between the electrode and the membrane, and the contact surface with the electrode plate. Summary of the invention

[0006] The main purpose of the present invention is to provide a hydrogen evolution electrode for the cathode of an AEM electrolytic cell, so as to solve the problem of hydrogen ion surface dissociation and corrosion in the AEM electrolytic cell under a strong alkaline environment.

[0007] Another object of the present invention is to provide a method for preparing the hydrogen evolution electrode for the cathode of the AEM electrolytic cell, which has a simple process and is easy to industrialize.

[0008] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect of the present invention, there is provided a hydrogen evolution electrode for an AEM electrolytic cell cathode, which comprises a base mesh, a metal bottom layer and a catalytic layer in sequence; The base mesh is selected from a stainless steel mesh or a nickel mesh; The metal bottom layer is formed on the base mesh by physical vapor deposition, and its material is selected from one or more of Ni, Ti, or its alloy, or its oxide; The catalytic layer is deposited on the metal base layer by physical vapor deposition, and includes a catalytic base layer, a catalytic middle layer and a catalytic outer layer in sequence, and the porosity increases gradually from the catalytic base layer to the catalytic outer layer. The material of the catalytic layer includes a metal oxide formed by a main element and a doping element, the main element is Ni, and the atomic mass percentage is >30%, and the doping element is selected from one or more of Fe, Co, Mo, Fe-Sn alloy, Ni-Co-Mo alloy, and Fe-Mo alloy, and the atomic mass percentage is 15%~30%.

[0009] More preferably, the porosity of the catalytic layer is: catalytic bottom layer <30%, catalytic middle layer <60%, catalytic outer layer >70%.

[0010] Preferably, the specific surface area of ​​the hydrogen evolution electrode for the cathode of the AEM electrolyzer is >150m 2 / g.

[0011] Preferably, the surface contact angle of the hydrogen evolution electrode for the cathode of the AEM electrolyzer is <60°.

[0012] Preferably, the physical vapor deposition method is selected from one or more of magnetron sputtering, evaporation, and multi-arc ion plating.

[0013] A second aspect of the present invention provides a method for preparing the hydrogen evolution electrode for the cathode of the AEM electrolyzer, comprising the following steps: (1) Acid etching and surface roughening of the base mesh; (2) forming a metal base layer on the roughened substrate by physical vapor deposition; (3) performing vacuum vapor deposition on the surface of the metal bottom layer to sequentially form a catalytic bottom layer, a catalytic middle layer and a catalytic outer layer by controlling the process conditions of physical vapor deposition to obtain a catalytic layer; wherein the process conditions include deposition current, deposition time and deposition bias to obtain a catalytic layer; (4) The catalyst layer is post-treated by plasma of doped elements to form a porous network structure.

[0014] Preferably, in step (1), the solution used for the acid etching surface roughening treatment is an oxalic acid etching solution, the etching time is 5 to 15 minutes, and the temperature is 40 to 50°C.

[0015] Preferably, in step (2), the metal bottom layer is a metal Ni bottom layer or a metal Ti bottom layer, which is prepared by physical vapor deposition, with a deposition temperature of 300° C., a deposition time of 10 to 15 minutes, and a deposition bias of 1500V.

[0016] Preferably, in step (3), the porosity of the catalyst layer increases from the inside to the outside, the deposition current is 0-20V, the deposition time is 10-30min, and the deposition bias is 100-1500V.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1) On the one hand, acid etching surface roughening treatment is used to improve the bonding strength of the electrode material on the surface. On the other hand, vacuum deposition is used to reduce the wastewater pollution problem caused by chemical plating and electroplating. Vacuum deposition and bottom layer design greatly improve the interface bonding strength.

[0018] 2) The outer and inner layers of the multilayer structure are made dense inside and high outside porosity by adjusting the content of doping elements and reducing the bias voltage. This improves the stability of the material while allowing the reaction substances in the catalytic outer layer to enter effectively, greatly improving the corrosion resistance and catalytic effect in an alkaline environment.

[0019] 3) Through the doping treatment of F, O, and N elements, the outer layer is rich in electrons, forming a multi-electron characteristic in the catalyst material. The material locally presents a negative electron characteristic, which makes it easier to obtain H proton adsorption in an alkaline environment, greatly improving the enrichment of metal element reactants in the catalyst material on the catalyst surface to produce reactions, greatly reducing the reaction overpotential, and improving the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the structure of the hydrogen evolution electrode for the cathode of the AEM electrolyzer in the embodiment.

[0021] Figure 2 This is a FIB-TEM transmission photograph of the hydrogen evolution electrode used as the cathode of the AEM electrolytic cell in the embodiment.

[0022] Figure 3 These are the polarization curves of the hydrogen evolution electrode used as the cathode of the AEM electrolyzer in Examples 1 and 2 and the untreated porous diffusion electrode.

[0023] Figure 4 The performance change of the hydrogen evolution electrode used as the cathode of the AEM electrolyzer in Example 1 after 5000 hours of endurance.

[0024] Figure 5 It is a schematic diagram of the structure of an AEM electrolytic cell in the prior art. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0026] Example 1 (1) Select a stainless steel mesh with uniform thickness as the hydrogen evolution electrode substrate and perform ultrasonic cleaning in ethanol and water to remove surface grease and surface debris. Fix the stainless steel mesh on a rack and immerse it in oxalic acid etching solution. The etching time is controlled to be 10 minutes and the temperature is 45°C. During the etching process, the solution is continuously stirred to promote uniform reaction.

[0027] (2) Fix the stainless steel mesh to the electrode holder, move it to the closed reaction chamber and evacuate the inside of it. When the vacuum is 5×10 -3 Pa, turn on the heater to heat to 300℃, keep warm for a while, then introduce reaction gases Ar, O2 and NH3 into the cavity through the gas path and pores to control Co, Ni and pure Fe targets respectively, and control the vacuum degree to 2Pa through the exhaust system; at a deposition temperature of 300℃, control the deposition current of Ni target to 1A, the deposition time to 10min, the deposition bias to 1500V, and deposit the metal Ni bottom layer.

[0028] (3) Controlling Co, Ni, and pure Fe targets, and performing vacuum vapor deposition under the conditions of a vacuum degree of 2 Pa and a deposition temperature of 300 ° C, first controlling the deposition current of the Ni target to 9 A, the deposition current of the pure Fe target to 3 A, the deposition current of the Co target to 1 A, the deposition time to 10 min, and the deposition bias to 1200 V; then controlling the deposition current of the Ni target to 9 A, the deposition current of the pure Fe target to 3 A, the deposition current of the Co target to 0.5 A, the deposition time to 30 min, and the deposition bias to 500 V; then controlling the deposition current of the Ni target to 9 A, the deposition current of the pure Fe target to 3 A, the deposition current of the Co target to 0 A, the deposition time to 30 min, and the deposition bias to 120 V; gradually cooling to room temperature to obtain Ni-Fe-CoO x Hydrogen evolution electrode, thickness is 1000nm.

[0029] (4) Prepared Ni-Fe-CoO x The hydrogen evolution electrode is moved to a closed reaction chamber and the interior is evacuated. When the vacuum is evacuated to 5×10 -3Pa, turn on the heater to heat to 600℃ and keep it warm for a while, then introduce the reaction gas NH3 into the cavity through the gas path and the pores, control the deposition bias voltage to 800-1200V, and post-treat at a deposition temperature of 600℃ for 60min. Figure 1 and 2 shown.

[0030] Electrode performance: Figure 3 As shown, the prepared Ni-Fe-CoO x The hydrogen evolution electrode is 5 cm 2 The cathode of the small battery is a porous diffusion electrode, and the anode is a commercial IR-O x The catalyst was polarized at different current densities. By comparing the cathode uncoated stainless steel felt material, it was found that the maximum current density of the electrode material without catalyst could only reach 0.4A / cm 2 , the voltage exceeds 2.2V, and the electrode material with catalytic material is 1A / cm 2 The lower voltage is reduced to 1.6V, which greatly reduces the overpotential.

[0031] Electrode stability performance: such as Figure 4 As shown, the prepared Ni-Fe-CoO x The hydrogen evolution electrode is 5 cm 2 The cathode of a small battery is a porous diffusion electrode, which is 1A / cm 2 After 5000h of stable operation, the polarization curve performance test found that 1A / cm 2 The lower voltage decays by 60mV, which is much lower than that of commercial AEM.

[0032] Example 2 (1) Select a nickel mesh with uniform thickness as the electrode substrate and perform ultrasonic cleaning in ethanol and water to remove surface grease and surface debris. Fix the nickel mesh on a rack and immerse it in oxalic acid etching solution. The etching time is controlled to be 10 minutes and the temperature is 45°C. During the etching process, the solution is continuously stirred to promote uniform reaction.

[0033] (2) Fix the nickel mesh to the electrode holder, move it to the closed reaction chamber and evacuate the inside of it. When the vacuum is evacuated to 5×10 -3 Pa, turn on the heater to heat to 300℃, keep warm for a while, then introduce reaction gases Ar and O2 into the cavity through the gas path and pores to control Ti, Ni, and Fe-Sn alloy targets respectively, and control the vacuum degree of the process to be 2Pa through the exhaust system. At the deposition temperature of 300℃, the deposition current of the Ti target is controlled to be 5A, the deposition time is 10min, the deposition bias is 1500V, and the metal Ti bottom layer is deposited.

[0034] (3) Control Ti, Ni, and Fe-Sn alloy targets respectively, and perform vacuum vapor deposition under the conditions of a vacuum degree of 2 Pa and a deposition temperature of 300 °C. First, control the deposition current of the Ni target to 10 A, the deposition current of the Fe-Sn alloy target to 3 A, the deposition time to 15 min, and the deposition bias to 1200 V; then control the deposition current of the Ni target to 10 A, the deposition current of the Fe-Sn alloy target to 2 A, the deposition time to 30 min, and the deposition bias to 500 V; then control the deposition current of the Ni target to 12 A, the deposition current of the Fe-Sn alloy target to 1 A, the deposition time to 45 min, and the deposition bias to 120 V; gradually cool to room temperature to obtain Ni-Fe-SnO x Hydrogen evolution electrode, thickness is 500nm.

[0035] (4) Prepared Ni-Fe-SnO x The hydrogen evolution electrode is moved to a closed reaction chamber and the interior is evacuated. When the vacuum is evacuated to 5×10 -3 Pa, turn on the heater and heat to 900℃, keep it warm for a while, then introduce the reaction gas PF3 into the cavity through the gas path and pores, control the vacuum degree at 0.2Pa, the deposition bias voltage at 700-1200V, and post-treat at a deposition temperature of 900℃ for 60min.

[0036] Electrode performance: Figure 3 As shown, the prepared Ni-Fe-SnO x The hydrogen evolution electrode is 5 cm 2 The cathode of the small battery is a porous diffusion electrode, and the anode is a commercial IR-O x The catalyst was polarized at different current densities. By comparing the cathode uncoated stainless steel felt material, it was found that the maximum current density of the electrode material without catalyst could only reach 0.4A / cm 2 , the voltage exceeds 2.2V, and the electrode material with catalytic material is 1A / cm 2 The lower voltage is reduced to 1.7V, greatly reducing the overpotential.

[0037] Example 3 (1) Select a nickel mesh with uniform thickness as the electrode substrate and perform ultrasonic cleaning in ethanol and water to remove surface grease and surface debris. Fix the nickel mesh on a rack and immerse it in oxalic acid etching solution. The etching time is controlled to be 10 minutes and the temperature is 45°C. During the etching process, the solution is continuously stirred to promote uniform reaction.

[0038] (2) Fix the nickel mesh to the electrode holder, move it to the closed reaction chamber and evacuate the inside of it. When the vacuum is evacuated to 5×10 -3Pa, turn on the heater and heat to 300℃, keep it warm for a while, then introduce reaction gases Ar and O2 into the cavity through the gas path and pores to control Ni and Ni-Co-Mo alloy targets respectively, and control the vacuum degree of the process to 2Pa through the exhaust system. At the deposition temperature of 300℃, the deposition current of the Ni target is controlled to be 5A, the deposition time is 10min, the deposition bias is 1500V, and the metal Ni bottom layer is deposited.

[0039] (3) Control Ni and Ni-Co-Mo alloy targets respectively, and perform vacuum vapor deposition under the conditions of vacuum degree of 2 Pa and deposition temperature of 300 °C: first control the deposition current of Ni target to 10 A, the deposition current of Ni-Co-Mo alloy target to 3 A, the deposition time to 30 min, and the deposition bias to 500 V; then control the deposition current of Ni target to 12 A, the deposition current of Ni-Co-Mo alloy target to 1 A, the deposition time to 40 min, and the deposition bias to 120 V, and gradually cool to room temperature to obtain Ni-Co-MoO x Hydrogen evolution electrode, thickness 500nm.

[0040] (4) Prepared Ni-Co-MoO x The hydrogen evolution electrode is moved to a closed reaction chamber and the interior is evacuated. When the vacuum is evacuated to 5×10 -3 Pa, turn on the heater to heat to 800℃ and keep it warm for a while, then introduce the reaction gas CF4 into the cavity through the gas path and pores, control the vacuum degree at 0.01Pa, the deposition bias is 1000V, and post-treat at a deposition temperature of 800℃ for 30min.

[0041] Example 4 (1) Select a nickel mesh with uniform thickness as the electrode substrate and perform ultrasonic cleaning in ethanol and water to remove surface grease and surface debris. Fix the nickel mesh on a rack and immerse it in oxalic acid etching solution. The etching time is controlled to be 10 minutes and the temperature is 45°C. During the etching process, the solution is continuously stirred to promote uniform reaction.

[0042] (2) Fix the nickel mesh to the electrode holder, move it to the closed reaction chamber and evacuate the inside of it. When the vacuum is evacuated to 5×10 -3 Pa, turn on the heater to heat to 300℃ and keep it warm for a while, then introduce reaction gases Ar and O2 into the cavity through the gas path and pores to control Ni and Fe-Mo alloy targets respectively, and control the vacuum degree of the process to 2Pa through the exhaust system, control the deposition current of Ni target to 5A at the deposition temperature of 300℃, the deposition time to 10min, the deposition bias to 1500V, and deposit the metal Ni bottom layer.

[0043] (3) Control Ni and Fe-Mo alloy targets respectively, and perform vacuum vapor deposition under the conditions of vacuum degree of 2Pa and deposition temperature of 300℃: first control the deposition current of Ni target to 9A, the deposition current of Fe-Mo alloy target to 3A, the deposition time to 10min, and the deposition bias to 1500V; then control the deposition current of Ni target to 12A, the deposition current of Fe-Mo alloy target to 2A, the deposition time to 30min, and the deposition bias to 500V; finally control the deposition current of Ni target to 12A, the deposition current of Fe-Mo alloy target to 2A, the deposition time to 40min, and the deposition bias to 120V, and gradually cool to room temperature to obtain hydrogen evolution Ni-Fe-CoO x Electrode, thickness 500nm; (4) Prepared Ni-Fe-CoO x The electrode was moved to a closed reaction chamber and the interior was evacuated. When the vacuum was evacuated to 5×10 -3 Pa, turn on the heater to heat to 800℃ and keep it warm for a while, then introduce the reaction gas CF4 into the cavity through the gas path and pores, control the vacuum degree at 0.01 Pa, the deposition bias is 1000 V, and post-treat at a deposition temperature of 800℃ for 30 min.

[0044] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A hydrogen evolution electrode for an AEM electrolyzer cathode, characterized in that: It includes a base mesh, a metal bottom layer and a catalytic layer in sequence; The base mesh is selected from a stainless steel mesh or a nickel mesh; The metal bottom layer is formed on the base mesh by physical vapor deposition, and its material is selected from one or more of Ni, Ti, or its alloy, or its oxide; The catalytic layer is deposited on the metal base layer by physical vapor deposition, and includes a catalytic base layer, a catalytic middle layer and a catalytic outer layer in sequence, and the porosity increases gradually from the catalytic base layer to the catalytic outer layer. The material of the catalytic layer includes a metal oxide formed by a main element and a doping element, the main element is Ni, and the atomic mass percentage is >30%, and the doping element is selected from one or more of Fe, Co, Mo, Fe-Sn alloy, Ni-Co-Mo alloy, and Fe-Mo alloy, and the atomic mass percentage is 15%~30%.

2. The hydrogen evolution electrode for the cathode of the AEM electrolyzer according to claim 1, characterized in that: The porosity of the catalytic layer is: catalytic bottom layer <30%, catalytic middle layer <60%, catalytic outer layer >70%.

3. The hydrogen evolution electrode for cathode of AEM electrolyzer according to claim 1, characterized in that: The specific surface area of ​​the hydrogen evolution electrode for the cathode of the AEM electrolyzer is>150m 2 / g.

4. The hydrogen evolution electrode for cathode of AEM electrolyzer according to claim 1, characterized in that: The surface contact angle of the hydrogen evolution electrode used for the cathode of the AEM electrolyzer is less than 60°.

5. The hydrogen evolution electrode for cathode of AEM electrolyzer according to claim 1, characterized in that: The physical vapor deposition method is selected from one or more of magnetron sputtering, evaporation, and multi-arc ion plating.

6. The method for preparing the hydrogen evolution electrode for the cathode of the AEM electrolyzer according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Acid etching and surface roughening of the base mesh; (2) forming a metal base layer on the roughened substrate by physical vapor deposition; (3) performing vacuum vapor deposition on the surface of the metal bottom layer to sequentially form a catalytic bottom layer, a catalytic middle layer and a catalytic outer layer by controlling the process conditions of physical vapor deposition to obtain a catalytic layer; wherein the process conditions include deposition current, deposition time and deposition bias to obtain a catalytic layer; (4) Post-treating the catalyst layer by plasma doping the element to form a porous network structure, thereby obtaining a hydrogen evolution electrode for the cathode of the AEM electrolyzer.

7. The method for preparing a hydrogen evolution electrode for an AEM electrolytic cell cathode according to claim 6, characterized in that: In step (1), the solution used for the acid etching surface roughening treatment is oxalic acid etching solution, the etching time is 5-15 minutes, and the temperature is 40-50°C.

8. The method for preparing a hydrogen evolution electrode for an AEM electrolytic cell cathode according to claim 6, characterized in that: In step (2), the metal bottom layer is a metal Ni bottom layer or a metal Ti bottom layer, which is prepared by physical vapor deposition, with a deposition temperature of 300° C., a deposition time of 10 to 15 minutes, and a deposition bias of 1500V.

9. The method for preparing a hydrogen evolution electrode for an AEM electrolytic cell cathode according to claim 6, characterized in that: In step (3), the porosity of the catalyst layer increases from the inside to the outside, the deposition current is 0-20V, the deposition time is 10-30min, and the deposition bias is 100-1500V.

Citation Information

Patent Citations

  • PEM electrolytic hydrogen production cathode diffusion layer and preparation method thereof

    CN117026272A

  • Cathode-catalyzed electrode producing method in coal electrolyzing, hydrogenizing and liquefying process

    CN101717951A

  • AEM electrolyzed water metal catalyst and preparation method and application thereof

    CN115261926A

  • Preparation method and application of AEMWE cathode catalyst under large current density

    CN118477697A

  • Negative electrode containing transition layer and used for hydrogen production by alkaline electrolysis of water

    CN118704037A

Cited By

  • Alkaline electrolytic water hydrogen production electrode, preparation method and application

    CN121321062A

  • Hydrogen electrode for alkaline electrolysis of water, method of preparation and use

    CN121321062B

  • Method of manufacturing stainless steel fiber paper for anion exchange membrane water electrolysis and anion exchange membrane water electrolysis device using stainless steel fiber paper

    TWI940250B